The Lost Journals of Sylvia Plath : a Novel - Knutsen, Kimberly (Switchgrass Books, 2015)
Finalist, 2015 Midwest Book Award Chicago Book Review Best Book of 2015 Set in the frozen wasteland of Midwestern academia, The Lost Journals of Sylvia Plath introduces Wilson A. Lavender, father of three, instructor of women's studies, and self-proclaimed genius who is beginning to think he knows nothing about women. He spends much of his time in his office not working on his dissertation, a creative piece titled "The Lost Journals of Sylvia Plath." A sober alcoholic, he also spends much of his time not drinking, until he hooks up with his office mate, Alice Cherry, an undercover stripper who introduces him to "the buffer"--The chemical solution to his woes. Wilson's wife, Katie, is an anxious hippie, genuine earth mother, and recent PhD with no plans other than to read People magazine, eat chocolate, and seduce her young neighbor--a community college student who has built a bar in his garage. Intelligent and funny, Katie is haunted by a violent childhood. Her husband's "tortured genius" both exhausts and amuses her. The Lavenders' stagnant world is roiled when Katie's pregnant sister, January, moves in. Obsessed with her lost love, '80s rocker Stevie Flame, January is on a quest to reconnect with her glittery, big-haired past. A free spirit to the point of using other people's toothbrushes without asking, she drives Wilson crazy. Exploring the landscape of family life, troubled relationships, dreams of the future, and nightmares of the past, Knutsen has conjured a literary gem filled with humor and sorrow, Aqua Net and Scooby-Doo, diapers and benzodiazepines--all the detritus and horror and beauty of modern life